EVALUATION OF CHARACTERISTICS OF HARDWARE IMPLEMENTATION OF SOME IMAGE FILTERING ALGORITHMS - A. S. Poljakov; V. E. Samsonov (Informatika, 2016)
Processing speed and hardware requirements of two popular image filtering algorithms in hardware implementation based on microchips of FPGA type are provided. A possibility of using algorithms for processing of standard frames of video sequences is considered.